Imported Cabbageworm, Pieris rapae (Linnaeus) (Insecta: Lepidoptera: Pieridae) - John L. Capinera (EDIS)
This document is EENY-126 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2000.